le Futur de l’allemand - Aude Rebotier (Corela)
Werden + infinitive is traditionally considered as the German future tense, but it has been much debated for a long time. Because of its competition with the Präsens, because it is less frequently used than other future tenses (like French future tenses), and because it carries various modal effects, its status as a Tense is regularly questioned. This article is based on the results of a corpus analysis. It examines the various arguments that could speak against its status as a Tense, and relativizes them by looking at the French tenses. It is possible to uphold that werden + infinitive is a tense without disregarding its specific use in German, if one admit that the German future tense is limited to the most typical uses of a future tense, i.e., those in which the paradox of every future tense is most apparent: the speaker commits himself to a fact that is not (yet) proved to be true.